Effect of intercropping to the diameter of girth of rubber tree / Nurul Farahana Ruslin - Ruslin, Nurul Farahana (Faculty of Plantation and Agrotechnology, 2018)
Hevea brasiliensis or rubber is the primary source of natural rubber. Rubber has been used for centuries in thousand ways. During initial phase of rubber tree plantation, the farmers planted other crop on the same piece of land which known as intercropping system. This case study was purpose to study the effect of intercropping system on the diameter of girth of rubber tree in two different area in Projek Getah Untuk Pribumi (GUP) in Kampung Orang Asli Tohor, Jelebu, Negeri Sembilan. The objective of this case study is to determine whether or not intercrop give an effect to the diameter of girth of rubber tree. One of the area consist of rubber tree planted with banana as an intercrop and the other area consist of rubber plantation only without intercropping system. Three years data are used in this case study from October 2013 until October 2016. This case study showed that there is an effect of intercrop on the diameter of girth of rubber since the statistical analysis showed that there is a significant difference in the diameter of girth of rubber tree between both areas. In conclusion, the intercropping system did affect the diameter of girth of rubber tree since the banana and rubber compete for the sources to live.